To solve the system of equations:
- \(-5x + 4y = 48\) (Equation 1)
- \(-5x - 8y = 24\) (Equation 2)
We can eliminate \(x\) by subtracting Equation 2 from Equation 1:
\[ (-5x + 4y) - (-5x - 8y) = 48 - 24 \]
Simplifying this gives:
\[ 4y + 8y = 24 \]
\[ 12y = 24 \]
Now, divide both sides by 12:
\[ y = 2 \]
Now that we have \(y\), we can substitute this value back into one of the original equations to find \(x\). We can use Equation 1:
\[ -5x + 4(2) = 48 \]
This simplifies to:
\[ -5x + 8 = 48 \]
Subtract 8 from both sides:
\[ -5x = 40 \]
Now, divide by -5:
\[ x = -8 \]
So the solution to the system is:
\[ (-8, 2) \]
Thus the correct response is:
\((−8, 2)\)